Evaluation of mandibular and maxillary second molar root canal anatomy in a Turkish subpopulation using cbct: comparison of briseno-marroquin and vertucci classifications - Güneç, Hüseyin Gürkan; Öreroğlu, İpek; Çağlar, Kemal; Cesur Aydın, Kader (My University, 2025)
Background: This retrospective study aims to characterise the root canal morphology of maxillary and mandibular second molars using cone-beam computed tomography (CBCT). The number of roots and canal configurations were evaluated using both the Vertucci and Benjamı´n Brisen˜ o Marroquı´n classification systems. Methods: A total of 1084 second molar images (523 maxillary; 266 right and 257 left side and 561 mandibular; 285 right and 276 left side) were evaluated from 320 CBCT scans analyzed for the Turkish subpopulation. CBCT imaging provided superior visualisation of root canal anatomy compared to periapical radiography. The findings revealed diverse root canal configurations, with variations observed even within the same population. Statistical analyses, including the chi-squared test, were used to assess correlations between root number and demographic variables such as age and sex. Results: According to Benjamı´n Brisen˜ o Marroquı´n classification system, the most common configuration for upper right three-rooted teeth mesial root was 3URM2−1 (n:66, 35.7%), for distal root was 3URM1 (n:169, 91.4%), and for palatal root was 3URM1 (n:165, 89.2%). Additionally, the most common configuration for upper left three-rooted teeth mesial root was 3271 (n:50, 28.4%), for distal root was 3ULM1 (n:160, 90.9%), and for palatal root was 3ULM1 (n:158, 89.8%). In lower left molars, the most common configuration in the two-rooted teeth mesial root was 2LLM2 (n:114, 49.4%), and for the distal root was 2LLM1 (n:170, 73.6%). For lower right the most common configuration for two-rooted teeth mesial root was 2LRM2 (n:125, 52.5%), and for distal root was 2LRM1 (n:173, 72.7%)(p < 0.05). Conclusion: The primary outcome was observed that the root canal anatomy of upper and lower second molars may differ in both classifications of Turkish subpopulation. While Vertucci's classification was inadequate in some cases, Briseno-Marroquin classification was able to classify all upper and lower second molars with a single code. This new classification is a more useful system for classifying all second molars. There is a statistically significant difference exists among the new configuration according to the distribution of the teeth analyzed.
Keywords: CBCT; Root Canal Morphology; Vertucci Classification; Benjamı´N Brisen˜ O Marroquı´N Classification; Second Molars